Theorizing the carceral: political economy, critical geography, and criminology - Shantz, Jeff (International sociology, 2017)
This review essay examines new works by Hadar Aviram on the political economy of penal policies and Dominique Moran on carceral geographies. It discusses how these works offer significant insights for understanding emerging policies and practices of the prison-industrial complex in conditions of neoliberal capitalism. An assessment of these works, in relation to some pressing real-world issues, suggests that new theorizing around the political economy of criminal justice systems and critical geographies of punitive practices makes important contributions to revitalizing criminological theory in the contemporary context.